2016
DOI: 10.1016/j.adro.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Preplanning prediction of the left anterior descending artery maximum dose based on patient, dosimetric, and treatment planning parameters

Abstract: PurposeMaximum dose to the left anterior descending artery (LADmax) is an important physical constraint to reduce the risk of cardiovascular toxicity. We generated a simple algorithm to guide the positioning of the tangent fields to reliably maintain LADmax <10 Gy.Methods and materialsDosimetric plans from 146 consecutive women treated prone to the left breast enrolled in prospective protocols of accelerated whole breast radiation therapy, with a concomitant daily boost to the tumor bed (40.5 Gy/15 fraction to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…These methods aim to predict single or a small number of dose metrics to either guide plan optimization or a specific planning decision (e.g., the need for hydrogel injection) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods aim to predict single or a small number of dose metrics to either guide plan optimization or a specific planning decision (e.g., the need for hydrogel injection) …”
Section: Resultsmentioning
confidence: 99%
“…One or more specific dose metrics (14 articles) These methods aim to predict single or a small number of dose metrics to either guide plan optimization or a specific planning decision (e.g., the need for hydrogel injection). 21,[43][44][45][46][47][48][49][50][51][52][53][54][55] 3. Voxel-level doses (13 articles) This group of methods predicts dose at each voxel in 3D space.…”
Section: Dose-volume Histogram (Dvh) (36 Articles)mentioning
confidence: 99%
“…10 Cooper et al suggested only 2.5 mm. 19 These protocols have the advantage of being simple, but they cannot be applied when using volumetric modulated arc therapy techniques because the fields are not static and constantly change. It is interesting to note that the delineation method was not described in any of these articles.…”
Section: Discussionmentioning
confidence: 99%
“…Lind et al 25 studied single-photon emission tomography myocardial perfusion imaging in 69 patients who underwent RT for left-sided BC and found perfusion defects in the LAD distribution, pointing to a likely mechanism of cardiac damage. Copper et al 26 suggested the maximum LAD dose (LAD max ) may be more clinically relevant over the mean LAD dose, as occlusion of only 1 section of the LAD can result in symptomatic heart disease and proposed LAD max < 10 Gy. Our patient’s LAD max was very close at 10.9 Gy.…”
Section: Discussionmentioning
confidence: 99%